Fisetin nanoparticles protect against PM2.5 exposure-induced neuroinflammation by down-regulation of astrocytes activation related NF-κB signaling pathway. (February 2020) - Xu, Min-Xuan; Ge, Chen-Xu; Li, Qiang; Lou, De-Shuai; Hu, Lin-Feng; Sun, Yan; Xiong, Ming-Xin; Lai, Li-Li; Zhong, Shao-Yu; Yi, Chao; Wang, Bo-Chu; Tan, Jun
Graphical abstract: Highlights: Fisetin nanoparticles inhibit PM2.5 exposures induced neuroinflammation. Fisetin nanoparticles restrain PM2.5 exposure-induced NF-κB signaling activation. Fisetin nanoparticles decrease PM2.5-induced astrocytes activation. Abstract: Astrocytes activation related NF-κB signaling and oxidative stress were treated as key target associated with PM2.5 threating nerve injury. Unfortunately, the underlying molecular mechanisms of interaction between NF-κB signaling, glial cells activation in neuroinflammation are still not absolutely explained. Fisetin, a natural flavonoid was found to be promote health, partly due to its ability in antioxidant and anti-inflammation. In this regard, we constructed fisetin nanoparticles (FN) to investigate the anti-inflammatory effect in PM2.5-induced mice. Accordingly, qPCR and western blot analysis indicated that astrocytes activation related NF-κB signaling and oxidative stress contributed to PM2.5-induced neuroinflammation, which were significantly suppressed by increasing concentration of FN treatment. Also, FN may directly enhance anti-oxidative stress and anti-inflammatory way to perform inhibitory effects on NF-κB related glial cells activation. Overall, here we identified a new mechanism of action of FN as potential anti-inflammatory product against PM2.5-induced neuroinflammation via regulation of astrocytes activation related NF-κB.